"Rospalcie nowe slonca..." : Agata Budzynska w piosenkach, listach, wywiadach, wspomnieniach - Budzynska, Agata; Bis, Ewa.; Mitrus, Dorota; Trabka, Andrzej (Lublin : Norbertinum, 1997)
A profile of Agata Budzynska in her songs, letters, interviews and memoirs. She wa a poet, composer and singer who died tragically at age 32 in 1996.
Keywords: Budzynska, Agata; Singers -- Poland -- Biography